THE INFLUENCE OF STORE ATMOSPHERE AND PRODUCT TASTE ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION AT SAMARA COFFEE PEKANBARU CONSUMERS - Prima, Ajeng Nur Otavia (JURNAL ILMU MANAJEMEN, 2023)
This research aims to determine the influence of Store Atmosphere and Product Taste on Repurchase Intention Through Customer Satisfaction at Samara Coffee Pekanbaru Consumers. The population in this study were all visitors to Samara Coffee Pekanbaru. The sampling technique used in this research is non-probability sampling technique using purposive sampling so that the number of samples used was 125 respondents. The data analysis method in this research uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS version 4.0 software . The research results show that (1) Store Atmosphere has a significant effect on Customer Satisfaction, (2) Product Taste has a significant effect on Customer Satisfaction, (3) Store Atmosphere has a significant effect on Repurchase Intention, (4) Product Taste has a significant effect on Repurchase Intention, (5) Customer Satisfaction has a significant effect on Repurchase Intention, (6) Store Atmosphere has a significant effect on Repurchase Intention through Customer Satisfaction, (7) Product Taste has a significant effect on Repurchase Intention through Customer Satisfaction.